The Implementation of Authentic Assessment on Reading Comprehension of the Tenth Grade Students of SMANN 8 Padang - Sesy Erlina Martika; M. Zaim (Universitas Negeri Padang, 2021)
Authentic assessment can help teachers to find out the extent to which students can apply their knowledge and skills in the context of real situations. This is because authentic assessment focuses on activities or tasks performed by students after all the knowledge and skills being taught are adapted to the actual context. The researcher conducted the implementation of authentic assessment on reading comprehension in the tenth grade. The population and sample of this study were tenth-grade students and English teachers at SMA 8 Padang. This research uses descriptive quantitative research. This study aims to understand the form of authentic reading assessment, the level of difficulty, and the problems faced by the teacher in implementing the authentic assessment. The research instruments were documentation, questionnaire, and interviews. The results of the study found that (1) 4 forms of authentic assessment of reading comprehension used by teachers at SMAN 8 Padang, (2) the level of difficulty in implementing authentic assessment of reading comprehension was easy carried out by students, and (3) several problems faced by teachers in implementing of authentic assessment on reading comprehension.